Critical Review of A SPATIAL TYPOLOGY OF HUMAN SETTLEMENTS AND THEIR CO2 EMISSIONS IN ENGLAND - Perennia, N (2021)
Critical review of the paper A SPATIAL TYPOLOGY OF HUMAN SETTLEMENTS AND THEIR CO2 EMISSIONS IN ENGLAND authored by Baiocchi, Creutzing, Minx, and Pichler.